Determinants of Brand Advocacy in Academia: Analyzing the Role of Service Quality and Lecturer Competence - Hendrasto, Nur; Purba, Asnan; Haidar, Abdullah; Herindar, Evania; Chairiyati, Fauziah (JURNAL AL-TANZIM, 2024)
This study delves into the interplay between the quality of educational services and lecturer competence at IAI TAZKIA and their effects on brand advocacy. Analyzing data from 305 graduates and students across seven cohorts (2015-2021) and academic disciplines, it employs structural equation modeling (SEM) to explore these dynamics. The findings reveal that while lecturer competence does not significantly impact brand advocacy, the quality of educational services does. Specifically, postgraduate programs are perceived to offer the highest service quality, whereas Islamic Accounting and Islamic Business Management are viewed less favorably. Islamic Broadcasting Communication, a new field, needs more specialized faculty. Regarding lecturer competence, postgraduate students report the highest levels, with Islamic Economics instructors deemed more competent than those in Sharia Accounting, despite the latter's "A" accreditation. Brand advocacy is lowest among Sharia Business Management graduates, whereas postgraduate programs see the highest engagement in brand advocacy efforts. The research aims to position the campus as a benchmark for improving lecturer competence and service quality, enhancing institutional brand advocacy and competitive standing.